Neutral ultrahigh-temperature-resistant low-dilution oil well cement paste retarder as well as preparation and application thereof
Deep wells and ultra-high temperature low dilution oil well cement retarder prepared by polymerization of 2-acrylamide-2-methylpropanesulfonic acid, econiconic acid and imidazolidinone in deep and ultra-deep wells were solved. The problems of too short settling time and poor high-temperature stability in ultra-deep wells have achieved extended thickening time and high-temperature salt resistance, meeting the cementing needs of deep wells and ultra-deep wells.
Patent Information
- Application Number
- CN202411270930.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to effectively extend the settling time of cement slurry in deep and ultra-deep wells, and the stability is poor in high-temperature environments, which affects the cementing quality and cannot meet the high-temperature salt resistance needs of deep and ultra-deep wells.
Using neutral anti-ultra-high temperature and low-dilution oil well cement retarder prepared from polymerization of 2-acrylamide-2-methylpropanesulfonic acid, econic acid and imidazolidinone, ensures retardation through specific formula ratios and preparation methods. The temperature resistance and low temperature and high temperature stability of the coagulant at above 240°C.
It extends the thickening time of cement slurry, has temperature resistance of above 240℃, and is not diluted at high temperatures, meeting the cementing needs of deep and ultra-deep wells, and provides good stability and environmental protection performance.
Abstract
Description
Technical Field
[0001] The invention relates to a neutral ultra-high temperature resistant and low dilution oil well cement slurry retarder and the preparation and application thereof. Background Art
[0002] Cementing is to inject cement into the annulus between the wellbore and the casing of the oil well, and after it solidifies, it forms cement stone to reinforce the wellbore wall, fix the casing and isolate the oil, gas and water layers, thereby ensuring the safety of drilling and reasonable oil and gas production throughout the entire mining process. Cementing is a major link in the construction of oil wells. The quality of cementing is directly related to the continued drilling of the well, as well as the quality of subsequent completion, oil production, well repair and other operations. Poor quality cementing operations can cause formation blockage, gas channeling, water channeling, reduced crude oil recovery and casing corrosion. The research and practice of cementing technology in the past decade have shown that good cementing can increase oil and gas production by 5-10%. Retarder is an admixture that can effectively delay the hydration reaction of cement, thereby prolonging the setting time of cement slurry, facilitating cement pouring, and improving work efficiency. At the same time, it will not have adverse effects on the various properties of cement stone in the later stage. It is one of the most important oil well cement admixtures. If the cement slurry thickening time is too short, it may cause the cementing operation to be "sausage-stuffed"; if the thickening time is too long, it may cause the liquid in the well to channel and the cementing quality to be poor, or the casing to fall off when re-drilling, and the early strength of the cement stone to be low. With the exhaustion of shallow oil, oil exploration and production are forced to develop in the direction of deep wells, ultra-deep wells, and special wells. The number of deep wells and ultra-deep wells drilled has increased year by year, and a large number of deep wells and ultra-deep wells have become the main source of oil production. Therefore, it is more and more urgent to develop high-temperature and salt-resistant retarders that can meet the needs of deep well and ultra-deep well cementing for deep well oil exploitation, and it has broad market prospects. Summary of the invention
[0003] The present invention provides a neutral ultra-high temperature resistant and low dilution oil well cement retarder, which is used for deep wells and ultra-deep wells, has a temperature resistance of 240°C and above, has no obvious dilution when the temperature is higher than 150°C, effectively prolongs the thickening time, has a large temperature difference resistance, meets the top strength requirement, has a neutral pH, does not thicken at low temperatures, has no flocculation or sedimentation at high temperatures, and can meet the cementing requirements of deep wells and ultra-deep wells.
[0004] As one aspect of the present invention, it relates to a neutral ultra-high temperature resistant low dilution oil well cement retarder, which is prepared by polymerization of 2-acrylamide-2-methylpropane sulfonic acid, itaconic acid and imidazolidinone, wherein the weight parts are 120-150 parts of 2-acrylamide-2-methylpropane sulfonic acid, 28-38 parts of itaconic acid and 5-10 parts of imidazolidinone respectively.
[0005] As another aspect of the present invention, it relates to a method for preparing the above-mentioned neutral ultra-high temperature resistant low dilution oil well cement retarder, the method comprising:
[0006] (1) Dissolve 120-150 parts of AMPS (2-acrylamide-2-methylpropanesulfonic acid), 28-38 parts of itaconic acid, 5-10 parts of imidazolidinone, 2-5 parts of sulfite and 5-10 parts of ammonium persulfate in 80-90 parts of water; (2) Add 0.5-1 parts of polycarboxylic acid water reducer and 0.7-1.2 parts of gluconate.
[0007] In a specific embodiment, step (1) preferably comprises dissolving 130-150 parts of AMPS, 35-38 parts of itaconic acid, 8-10 parts of imidazolidinone, 4-5 parts of sulfite and 8.5-10 parts of ammonium persulfate in 80-90 parts of water.
[0008] In a specific embodiment, step (2) preferably comprises 0.85-1 parts of polycarboxylate water reducer and 0.85-1.2 parts of gluconate.
[0009] In a specific embodiment, step (2) is preferably reacted at 78-80 degrees Celsius.
[0010] In a specific embodiment, the sulfite is sodium sulfite.
[0011] In a specific embodiment, the gluconate is sodium gluconate.
[0012] As another aspect of the present invention, it relates to the application of the above-mentioned neutral ultra-high temperature resistant and low dilution oil well cement retarder in oil and gas development.
[0013] As another aspect of the present invention, it relates to an oil well cement, wherein the oil well cement contains the above-mentioned neutral ultra-high temperature resistant and low dilution oil well cement retarder.
[0014] As another aspect of the present invention, it relates to the application of the above-mentioned oil well cement in oil and gas development.
[0015] The ultra-high temperature resistant and low dilution oil well cement retarder provided by the present invention has an adjustable thickening time, good compatibility with other admixtures, good stability without the need for additional suspension stabilizing materials, temperature resistance above 240°C, certain dosage sensitivity, effective extension of thickening time, resistance to large temperature differences, meeting top strength requirements, neutral pH, meeting environmental protection requirements, and the slurry does not thicken at low temperatures and does not flocculate or settle at high temperatures, thereby meeting the cementing requirements of deep wells and ultra-deep wells. DETAILED DESCRIPTION
[0016] The parts referred to in this application are parts by mass unless otherwise specified.
[0017] Example 1: Take 100 parts of AMPS (2-acrylamide-2-methylpropanesulfonic acid), 10 parts of itaconic acid, 5 parts of imidazolidinone, 0.5 parts of sodium sulfite, 0.1 parts of ammonium persulfate, 0.5 parts of polycarboxylate water reducer, 0.5 parts of sodium gluconate, and 80 parts of water.
[0018] In 80 parts of water, add 100 parts of AMPS, 10 parts of itaconic acid, heat to 70 degrees Celsius, add 5 parts of imidazolidinone, 0.5 parts of sodium sulfite, 0.1 parts of ammonium persulfate, fully dissolve, heat to 75 degrees Celsius, keep warm for 2 hours, add 0.5 parts of polycarboxylic acid water reducer and 0.5 parts of sodium gluconate, after adding, the temperature rises to 80 degrees Celsius, record the temperature and set the temperature section to keep warm for 4 hours to prepare the retarder. After the insulation is completed, cool to room temperature, and measure the polymer pH to be 6.9, which is neutral and meets environmental protection requirements.
[0019] Performance evaluation: The cement-based slurry (blank control group) was: 500g of G-grade cement + 300g of quartz sand + 336g of distilled water + 1.6g of GWX-1L.
[0020] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0021] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0022] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were recorded and entered into Table 1.
[0023] Table 1
[0024] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 86 22.3 Experimental Group 1 ---- ---- Experimental Group 2 ---- ----
[0025] As can be seen from Table 1, the slurry could not be poured into the slurry cup of the viscometer, and the evaluation experiment could not be carried out. The retarder was incompatible with the cement.
[0026] When the salt concentration increases, the slurry cannot be poured into the thickener cup and the evaluation experiment cannot be performed.
[0027] Example 2: Take 150 parts of AMPS (2-acrylamide-2-methylpropanesulfonic acid), 40 parts of itaconic acid, 15 parts of imidazolidinone, 1.0 part of sodium sulfite, 10 parts of ammonium persulfate, 1.0 part of polycarboxylic acid water reducer, 1.5 parts of sodium gluconate, and 80 parts of water.
[0028] In 80 parts of water, add 150 parts of AMPS, 40 parts of itaconic acid, heat to 70 degrees Celsius, add 15 parts of imidazolidinone, 1.0 part of sodium sulfite, 10 parts of ammonium persulfate, fully dissolve, heat to 75 degrees Celsius, keep warm for 2 hours, add 1.0 part of polycarboxylic acid water reducer and 1.5 parts of sodium gluconate, the temperature rises to 80 degrees Celsius after adding, record the temperature and set the temperature section to keep warm for 4 hours to prepare the retarder. After the insulation is completed, cool to room temperature, and the polymer pH is measured to be 2.9, which does not meet environmental protection requirements.
[0029] Performance evaluation: The cement-based slurry (blank control group) was: 500g of G-grade cement + 300g of quartz sand + 336g of distilled water + 1.6g of GWX-1L.
[0030] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0031] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0032] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and entered into Table 2.
[0033] Table 2
[0034] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 86 22.3 Experimental Group 1 ---- ---- Experimental Group 2 ---- ----
[0035] As can be seen from Table 2, the slurry could not be poured into the slurry cup of the viscometer, and the evaluation experiment could not be carried out. The retarder was incompatible with the cement.
[0036] When the salt concentration increases, the slurry cannot be poured into the viscometer slurry cup and the evaluation experiment cannot be carried out.
[0037] Example 3: Take 130 parts of AMPS (2-acrylamide-2-methylpropanesulfonic acid), 20 parts of itaconic acid, 15 parts of imidazolidinone, 5 parts of sodium sulfite, 5 parts of ammonium persulfate, 1.0 part of polycarboxylic acid water reducer, 1.5 parts of sodium gluconate, and 80 parts of water.
[0038] In 80 parts of water, 130 parts of AMPS and 20 parts of itaconic acid were added and heated to 70 degrees Celsius, 15 parts of imidazolidinone, 10 parts of sodium sulfite, and 10 parts of ammonium persulfate were added and fully dissolved, and the temperature was raised to 75 degrees Celsius. After keeping warm for 2 hours, 1.0 parts of polycarboxylic acid water reducer and 1.5 parts of sodium gluconate were added. After adding, the temperature was raised to 80 degrees Celsius, the temperature was recorded and the temperature section was set to keep warm for 4 hours to prepare a retarder. After the insulation was completed, it was cooled to room temperature and the polymer pH was measured to be 5.7, which did not meet environmental protection requirements.
[0039] Performance evaluation: The cement-based slurry (blank control group) was: 500g of G-grade cement + 300g of quartz sand + 336g of distilled water + 1.6g of GWX-1L.
[0040] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0041] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0042] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and included in Table 3.
[0043] Table 3
[0044] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 86 22.3 Experimental Group 1 127 20.7 Experimental Group 2 ---- ----
[0045] As shown in Table 3, the thickening time of the slurry with the retarder is prolonged, but the pH value does not meet the environmental protection requirements.
[0046] When the salt concentration increases, the slurry cannot be poured into the thickener cup and the evaluation experiment cannot be performed.
[0047] Example 4: Take 140 parts of AMPS (2-acrylamide-2-methylpropanesulfonic acid), 30 parts of itaconic acid, 12 parts of imidazolidinone, 6 parts of sodium sulfite, 8 parts of ammonium persulfate, 1.5 parts of polycarboxylic acid water reducer, 0.9 parts of sodium gluconate, and 80 parts of water.
[0048] In 80 parts of water, 140 parts of AMPS and 30 parts of itaconic acid were added and heated to 70 degrees Celsius, 12 parts of imidazole, 6 parts of sodium sulfite, and 8 parts of ammonium persulfate were added and fully dissolved, and the temperature was raised to 75 degrees Celsius. After 2 hours of heat preservation, 1.5 parts of polycarboxylic acid water reducer and 0.9 parts of sodium gluconate were added. After the addition, the temperature was raised to 80 degrees Celsius, the temperature was recorded and the temperature section was set to be kept warm for 4 hours to obtain a retarder. After the heat preservation was completed, it was cooled to room temperature and the polymer pH was measured to be 3.5, which did not meet environmental protection requirements.
[0049] Performance evaluation: The cement-based slurry (blank control group) was: 500g of G-grade cement + 300g of quartz sand + 336g of distilled water + 1.6g of GWX-1L.
[0050] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0051] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0052] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and included in Table 4.
[0053] Table 4
[0054] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 86 22.3 Experimental Group 1 96 12.5 Experimental Group 2 ---- ----
[0055] As shown in Table 4, the thickening time of the slurry with the retarder is prolonged, but the pH value does not meet the environmental protection requirements.
[0056] When the salt concentration increases, the slurry cannot be poured into the viscometer slurry cup and the evaluation experiment cannot be carried out.
[0057] Example 5: Take 150 parts of AMPS (2-acrylamide-2-methylpropanesulfonic acid), 28 parts of itaconic acid, 12 parts of imidazolidinone, 6 parts of sodium sulfite, 6 parts of ammonium persulfate, 1.5 parts of polycarboxylic acid water reducer, 1.5 parts of sodium gluconate, and 80 parts of water.
[0058] In 80 parts of water, 150 parts of AMPS and 28 parts of itaconic acid were added and heated to 70 degrees Celsius. 12 parts of imidazole, 6 parts of sodium sulfite, and 6 parts of ammonium persulfate were added and fully dissolved. The temperature was raised to 75 degrees Celsius. After 2 hours of heat preservation, 1.5 parts of polycarboxylate water reducer and 1.5 parts of sodium gluconate were added. After the addition, the temperature was raised to 80 degrees Celsius. The temperature was recorded and the temperature section was set to be kept warm for 4 hours to obtain a retarder. After the heat preservation was completed, it was cooled to room temperature and the polymer pH was measured to be 4.7, which did not meet environmental protection requirements.
[0059] Performance evaluation: The cement-based slurry (blank control group) was: 500g of G-grade cement + 300g of quartz sand + 336g of distilled water + 1.6g of GWX-1L.
[0060] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0061] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0062] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and included in Table 5.
[0063] Table 5
[0064] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 86 22.3 Experimental Group 1 150 18.2 Experimental Group 2 ---- ----
[0065] It can be seen from Table 5 that the thickening time of the slurry with the retarder is prolonged, but the pH does not meet the environmental protection requirements.
[0066] When the salt concentration increases, the slurry cannot be poured into the viscometer slurry cup and the evaluation experiment cannot be carried out.
[0067] Example 6: Take 150 parts of AMPS (2-acrylamide-2-methylpropanesulfonic acid), 25 parts of itaconic acid, 10 parts of imidazolidinone, 5 parts of sodium sulfite, 10 parts of ammonium persulfate, 0.5 parts of polycarboxylic acid water reducer, 1.5 parts of sodium gluconate, and 80 parts of water.
[0068] In 80 parts of water, add 150 parts of AMPS, 25 parts of itaconic acid, heat to 70 degrees Celsius, add 10 parts of imidazolidinone, 5 parts of sodium sulfite, 10 parts of ammonium persulfate, fully dissolve, heat to 75 degrees Celsius, keep warm for 2 hours, add 0.5 parts of polycarboxylate water reducer and 1.5 parts of sodium gluconate, the temperature rises to 80 degrees Celsius after adding, record the temperature and set the temperature section to keep warm for 4 hours to prepare the retarder. After the insulation is completed, cool to room temperature, and the polymer pH is measured to be 5.2, which does not meet environmental protection requirements.
[0069] Performance evaluation: The cement-based slurry (blank control group) was: 500g of G-grade cement + 300g of quartz sand + 336g of distilled water + 1.6g of GWX-1L.
[0070] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0071] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0072] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and included in Table 6.
[0073] Table 6
[0074] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 86 22.3 Experimental Group 1 126 13.2 Experimental Group 2 56 10.3
[0075] It can be seen from Table 6 that the thickening time of the slurry with the retarder is prolonged, but the pH does not meet the environmental protection requirements.
[0076] When the salt concentration increases, the thickening time of the slurry does not extend, indicating that the prepared retarder has temperature resistance but no salt resistance.
[0077] Example 7: Take 150 parts of AMPS (2-acrylamide-2-methylpropanesulfonic acid), 25 parts of itaconic acid, 10 parts of imidazolidinone, 5 parts of sodium sulfite, 10 parts of ammonium persulfate, 0.5 parts of polycarboxylic acid water reducer, 1.5 parts of sodium gluconate, and 80 parts of water.
[0078] In 80 parts of water, add 150 parts of AMPS, 25 parts of itaconic acid, heat to 70 degrees Celsius, add 10 parts of imidazolidinone, 5 parts of sodium sulfite, 10 parts of ammonium persulfate, fully dissolve, heat to 75 degrees Celsius, keep warm for 2 hours, add 0.5 parts of polycarboxylate water reducer and 1.5 parts of sodium gluconate, the temperature rises to 80 degrees Celsius after adding, record the temperature and set the temperature section to keep warm for 4 hours to prepare the retarder. After the insulation is completed, cool to room temperature, and the polymer pH is measured to be 5.2, which does not meet environmental protection requirements.
[0079] Performance evaluation: The cement-based slurry (blank control group) was: 500g of G-grade cement + 300g of quartz sand + 336g of distilled water + 1.6g of GWX-1L.
[0080] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0081] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0082] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and included in Table 7.
[0083] Table 7
[0084] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 86 22.3 Experimental Group 1 126 13.2 Experimental Group 2 56 10.3
[0085] It can be seen from Table 7 that the thickening time of the slurry with the retarder is prolonged, but the pH does not meet the environmental protection requirements.
[0086] When the salt concentration increases, the thickening time of the slurry does not extend, indicating that the prepared retarder has temperature resistance but no salt resistance.
[0087] Example 8: Take 150 parts of AMPS (2-acrylamide-2-methylpropanesulfonic acid), 25 parts of itaconic acid, 10 parts of imidazolidinone, 5 parts of sodium sulfite, 10 parts of ammonium persulfate, 0.5 parts of polycarboxylic acid water reducer, 1.5 parts of sodium gluconate, and 90 parts of water.
[0088] In 90 parts of water, 150 parts of AMPS and 25 parts of itaconic acid were added and heated to 70 degrees Celsius. 10 parts of imidazolidinone, 5 parts of sodium sulfite, and 10 parts of ammonium persulfate were added and fully dissolved. The temperature was raised to 75 degrees Celsius. After keeping warm for 2 hours, 0.5 parts of polycarboxylic acid water reducer and 1.5 parts of sodium gluconate were added. After adding, the temperature was raised to 80 degrees Celsius. The temperature was recorded and the temperature section was set to keep warm for 4 hours to obtain a retarder. After the insulation was completed, it was cooled to room temperature and the polymer pH was measured to be 5.6, which did not meet environmental protection requirements.
[0089] Performance evaluation: The cement-based slurry (blank control group) was: 500g of G-grade cement + 300g of quartz sand + 336g of distilled water + 1.6g of GWX-1L.
[0090] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0091] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0092] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and included in Table 8.
[0093] Table 8
[0094] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 86 22.3 Experimental Group 1 110 12.6 Experimental Group 2 58 10.2
[0095] It can be seen from Table 8 that the thickening time of the slurry with the retarder prepared is prolonged, but the pH does not meet the environmental protection requirements.
[0096] When the salt concentration increases, the thickening time of the slurry does not extend, indicating that the prepared retarder has temperature resistance but no salt resistance.
[0097] Example 9: Take 130 parts of AMPS (2-acrylamide-2-methylpropanesulfonic acid), 28 parts of itaconic acid, 5 parts of imidazolidinone, 2 parts of sodium sulfite, 5 parts of ammonium persulfate, 0.5 parts of polycarboxylic acid water reducer, 0.7 parts of sodium gluconate, and 100 parts of water.
[0098] In 100 parts of water, 130 parts of AMPS and 28 parts of itaconic acid were added and heated to 70 degrees Celsius. 5 parts of imidazolidinone, 2 parts of sodium sulfite, and 5 parts of ammonium persulfate were added and fully dissolved. The temperature was raised to 75 degrees Celsius. After 2 hours of heat preservation, 0.5 parts of polycarboxylic acid water reducer and 0.7 parts of sodium gluconate were added. After the addition, the temperature was raised to 80 degrees Celsius. The temperature was recorded and the temperature section was set to be kept warm for 4 hours to obtain a retarder. After the heat preservation was completed, it was cooled to room temperature and the polymer pH was measured to be 5.6, which did not meet environmental protection requirements.
[0099] Performance evaluation: The cement-based slurry (blank control group) was: 500g of G-grade cement + 300g of quartz sand + 336g of distilled water + 1.6g of GWX-1L.
[0100] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0101] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0102] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and entered into Table 9.
[0103] Table 9
[0104] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 86 22.3 Experimental Group 1 120 9.9 Experimental Group 2 60 8.6
[0105] It can be seen from Table 9 that the thickening time of the slurry with the retarder prepared is prolonged, but the pH does not meet the environmental protection requirements.
[0106] When the salt concentration increases, the thickening time of the slurry does not extend, indicating that the prepared retarder has temperature resistance but no salt resistance.
[0107] Example 10: Take 120 parts of AMPS (2-acrylamide-2-methylpropanesulfonic acid), 28 parts of itaconic acid, 6 parts of imidazolidinone, 3 parts of sodium sulfite, 5 parts of ammonium persulfate, 1.5 parts of polycarboxylic acid water reducer, 0.7 parts of sodium gluconate, and 80 parts of water.
[0108] In 80 parts of water, add 120 parts of AMPS, 28 parts of itaconic acid, heat to 70 degrees Celsius, add 6 parts of imidazolidinone, 3 parts of sodium sulfite, 5 parts of ammonium persulfate, fully dissolve, heat to 75 degrees Celsius, keep warm for 2 hours, add 1.5 parts of polycarboxylate water reducer and 0.7 parts of sodium gluconate, the temperature rises to 80 degrees Celsius after adding, record the temperature and set the temperature section to keep warm for 4 hours to prepare the retarder. After the insulation is completed, cool to room temperature, and the polymer pH is measured to be 6.9, which meets environmental protection requirements.
[0109] Performance evaluation: The cement-based slurry (blank control group) was: 500g of G-grade cement + 300g of quartz sand + 336g of distilled water + 1.6g of GWX-1L.
[0110] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0111] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0112] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and entered into Table 10.
[0113] Table 10
[0114] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 86 22.3 Experimental Group 1 137 5.6 Experimental Group 2 100 4.5
[0115] As shown in Table 10, the thickening time of the slurry with the retarder is prolonged. When the salt concentration increases, the thickening time of the slurry is prolonged, which indicates that the retarder has both temperature resistance and salt resistance. However, the strength decline is obvious.
[0116] Example 11: Take 125 parts of AMPS (2-acrylamide-2-methylpropanesulfonic acid), 30 parts of itaconic acid, 7 parts of imidazolidinone, 4 parts of sodium sulfite, 5 parts of ammonium persulfate, 0.5 parts of polycarboxylic acid water reducer, 0.7 parts of sodium gluconate, and 80 parts of water.
[0117] In 80 parts of water, add 125 parts of AMPS, 30 parts of itaconic acid, heat to 70 degrees Celsius, add 7 parts of imidazolidinone, 4 parts of sodium sulfite, 5 parts of ammonium persulfate, fully dissolve, heat to 75 degrees Celsius, keep warm for 2 hours, add 0.5 parts of polycarboxylate water reducer and 0.7 parts of sodium gluconate, after adding, the temperature rises to 80 degrees Celsius, record the temperature and set the temperature section to keep warm for 4 hours to prepare the retarder. After the insulation is completed, cool to room temperature, and the polymer pH is measured to be 6.9, which meets environmental protection requirements.
[0118] Performance evaluation: The cement-based slurry (blank control group) was: 500g of G-grade cement + 300g of quartz sand + 336g of distilled water + 1.6g of GWX-1L.
[0119] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0120] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0121] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and entered into Table 11.
[0122] Table 11
[0123] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 86 22.3 Experimental Group 1 104 9.2 Experimental Group 2 99 6.2
[0124] It can be seen from Table 11 that the thickening time of the slurry with the prepared retarder is prolonged. When the salt concentration increases, the thickening time of the slurry is prolonged, which shows that the prepared retarder has both temperature resistance and salt resistance, but the strength declines significantly.
[0125] Example 12: Take 135 parts of AMPS (2-acrylamide-2-methylpropanesulfonic acid), 32 parts of itaconic acid, 8 parts of imidazolidinone, 5 parts of sodium sulfite, 6 parts of ammonium persulfate, 0.5 parts of polycarboxylic acid water reducer, 0.8 parts of sodium gluconate, and 80 parts of water.
[0126] In 80 parts of water, add 135 parts of AMPS, 32 parts of itaconic acid, heat to 70 degrees Celsius, add 8 parts of imidazolidinone, 5 parts of sodium sulfite, 6 parts of ammonium persulfate, fully dissolve, heat to 75 degrees Celsius, keep warm for 2 hours, add 0.5 parts of polycarboxylate water reducer and 0.8 parts of sodium gluconate, the temperature rises to 80 degrees Celsius after adding, record the temperature and set the temperature section to keep warm for 4 hours to prepare the retarder. After the insulation is completed, cool to room temperature, and the polymer pH is measured to be 6.9, which meets environmental protection requirements.
[0127] Performance evaluation: The cement-based slurry (blank control group) was: 500g of G-grade cement + 300g of quartz sand + 336g of distilled water + 1.6g of GWX-1L.
[0128] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0129] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0130] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and entered into Table 12.
[0131] Table 12
[0132] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 86 22.3 Experimental Group 1 112 9.4 Experimental Group 2 103 6.8
[0133] As shown in Table 11, the thickening time of the slurry with the retarder is prolonged. When the salt concentration increases, the thickening time of the slurry is prolonged, which indicates that the retarder has both temperature resistance and salt resistance. However, the strength decline is obvious.
[0134] Example 13: Take 140 parts of AMPS (2-acrylamide-2-methylpropanesulfonic acid), 32 parts of itaconic acid, 9 parts of imidazolidinone, 5 parts of sodium sulfite, 7 parts of ammonium persulfate, 0.7 parts of polycarboxylic acid water reducer, 0.9 parts of sodium gluconate, and 80 parts of water.
[0135] In 80 parts of water, add 140 parts of AMPS, 32 parts of itaconic acid, heat to 70 degrees Celsius, add 9 parts of imidazolidinone, 5 parts of sodium sulfite, 7 parts of ammonium persulfate, fully dissolve, heat to 75 degrees Celsius, keep warm for 2 hours, add 0.7 parts of polycarboxylate water reducer and 0.9 parts of sodium gluconate, the temperature rises to 80 degrees Celsius after adding, record the temperature and set the temperature section to keep warm for 4 hours to prepare the retarder. After the insulation is completed, cool to room temperature, and the polymer pH is measured to be 6.9, which meets environmental protection requirements.
[0136] Performance evaluation: The cement-based slurry (blank control group) was: 500g of G-grade cement + 300g of quartz sand + 336g of distilled water + 1.6g of GWX-1L.
[0137] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0138] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0139] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and entered into Table 13.
[0140] Table 13
[0141] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 86 22.3 Experimental Group 1 142 10.2 Experimental Group 2 121 7.8
[0142] As shown in Table 13, the thickening time of the slurry with the retarder is prolonged. When the salt concentration increases, the thickening time of the slurry is prolonged, which indicates that the retarder has both temperature resistance and salt resistance. However, the strength decline is obvious.
[0143] Example 14: Take 145 parts of AMPS (2-acrylamide-2-methylpropanesulfonic acid), 34 parts of itaconic acid, 9 parts of imidazolidinone, 5 parts of sodium sulfite, 7 parts of ammonium persulfate, 0.7 parts of polycarboxylic acid water reducer, 0.9 parts of sodium gluconate, and 80 parts of water.
[0144] In 80 parts of water, add 145 parts of AMPS, 34 parts of itaconic acid, heat to 70 degrees Celsius, add 9 parts of imidazolidinone, 5 parts of sodium sulfite, 7 parts of ammonium persulfate, fully dissolve, heat to 75 degrees Celsius, keep warm for 2 hours, add 0.7 parts of polycarboxylate water reducer and 0.9 parts of sodium gluconate, the temperature rises to 80 degrees Celsius after adding, record the temperature and set the temperature section to keep warm for 4 hours to prepare the retarder. After the insulation is completed, cool to room temperature, and the polymer pH is measured to be 7.0, which meets environmental protection requirements.
[0145] Performance evaluation: The cement-based slurry (blank control group) was: 500g of G-grade cement + 300g of quartz sand + 336g of distilled water + 1.6g of GWX-1L.
[0146] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0147] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0148] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and entered into Table 14.
[0149] Table 14
[0150] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 86 22.3 Experimental Group 1 189 11.2 Experimental Group 2 142 7.6
[0151] As shown in Table 14, the thickening time of the slurry with the retarder is prolonged. When the salt concentration increases, the thickening time of the slurry is prolonged, indicating that the retarder has both temperature resistance and salt resistance. However, the strength decline is obvious.
[0152] Example 15: Take 150 parts of AMPS (2-acrylamide-2-methylpropanesulfonic acid), 38 parts of itaconic acid, 10 parts of imidazolidinone, 5 parts of sodium sulfite, 8 parts of ammonium persulfate, 0.7 parts of polycarboxylic acid water reducer, 0.9 parts of sodium gluconate, and 80 parts of water.
[0153] In 80 parts of water, add 150 parts of AMPS, 38 parts of itaconic acid, heat to 70 degrees Celsius, add 10 parts of imidazole, 5 parts of sodium sulfite, 8 parts of ammonium persulfate, fully dissolve, heat to 75 degrees Celsius, keep warm for 2 hours, add 0.7 parts of polycarboxylate water reducer and 0.9 parts of sodium gluconate, the temperature rises to 80 degrees Celsius after adding, record the temperature and set the temperature section to keep warm for 4 hours to prepare the retarder. After the insulation is completed, cool to room temperature, and the polymer pH is measured to be 7.0, which meets environmental protection requirements.
[0154] Performance evaluation: The cement-based slurry (blank control group) was: 500g of G-grade cement + 300g of quartz sand + 336g of distilled water + 1.6g of GWX-1L.
[0155] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0156] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0157] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and entered into Table 15.
[0158] Table 15
[0159] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 86 22.3 Experimental Group 1 197 13.1 Experimental Group 2 156 8.4
[0160] As shown in Table 15, the thickening time of the slurry with the prepared retarder is prolonged. When the salt concentration increases, the thickening time of the slurry is prolonged, indicating that the prepared retarder has both temperature resistance and salt resistance. The slurry has the properties of not thickening at low temperatures and not diluting at high temperatures.
[0161] Example 16: Take 120 parts of AMPS (2-acrylamide-2-methylpropanesulfonic acid), 28 parts of itaconic acid, 5 parts of imidazolidinone, 2 parts of sodium sulfite, 5 parts of ammonium persulfate, 0.5 parts of polycarboxylic acid water reducer, 0.7 parts of sodium gluconate, and 90 parts of water.
[0162] In 90 parts of water, add 120 parts of AMPS, 28 parts of itaconic acid, heat to 70 degrees Celsius, add 5 parts of imidazolidinone, 2 parts of sodium sulfite, 5 parts of ammonium persulfate, fully dissolve, heat to 75 degrees Celsius, keep warm for 2 hours, add 0.5 parts of polycarboxylate water reducer and 0.7 parts of sodium gluconate, the temperature rises to 80 degrees Celsius after adding, record the temperature and set the temperature section to keep warm for 4 hours to prepare the retarder. After the insulation is completed, cool to room temperature, and the polymer pH is measured to be 7.0, which meets environmental protection requirements.
[0163] Performance evaluation: The cement-based slurry (blank control group) was: 500g of G-grade cement + 300g of quartz sand + 336g of distilled water + 1.6g of GWX-1L.
[0164] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0165] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0166] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and entered into Table 16.
[0167] Table 16
[0168] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 86 22.3 Experimental Group 1 222 13.2 Experimental Group 2 180 9.3
[0169] It can be seen from Table 16 that the thickening time of the slurry with the retarder added is prolonged, and the thickening time of the slurry is prolonged when the salt concentration increases, indicating that the retarder prepared has both temperature and salt resistance, and the slurry has the properties of not thickening at low temperatures and not diluting at high temperatures.
[0170] Example 17: Take 130 parts of AMPS (2-acrylamide-2-methylpropanesulfonic acid), 35 parts of itaconic acid, 8 parts of imidazolidinone, 4 parts of sodium sulfite, 8.5 parts of ammonium persulfate, 0.85 parts of polycarboxylic acid water reducer, 0.85 parts of sodium gluconate, and 90 parts of water.
[0171] In 90 parts of water, 130 parts of AMPS and 35 parts of itaconic acid were added and heated to 70 degrees Celsius, 8 parts of imidazolidinone, 4 parts of sodium sulfite, and 8.5 parts of ammonium persulfate were added and fully dissolved, and the temperature was raised to 75 degrees Celsius. After 2 hours of heat preservation, 0.85 parts of polycarboxylic acid water reducer and 0.85 parts of sodium gluconate were added. After the addition, the temperature was raised to 78 degrees Celsius, the temperature was recorded and the temperature section was set to be kept warm for 4 hours to obtain a retarder. After the heat preservation was completed, it was cooled to room temperature, and the polymer pH was measured to be 7.0, which met the environmental protection requirements.
[0172] Performance evaluation: The cement-based slurry (blank control group) was: 500g of G-grade cement + 300g of quartz sand + 336g of distilled water + 1.6g of GWX-1L.
[0173] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0174] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0175] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and entered into Table 17.
[0176] Table 17
[0177] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 86 22.3 Experimental Group 1 210 10.0 Experimental Group 2 210 10.2
[0178] As shown in Table 15, the thickening time of the slurry with the prepared retarder is prolonged. When the salt concentration increases, the thickening time of the slurry is prolonged, indicating that the prepared retarder has both temperature resistance and salt resistance. The slurry has the properties of not thickening at low temperatures and not diluting at high temperatures.
[0179] Example 18: Take 130 parts of AMPS (2-acrylamide-2-methylpropanesulfonic acid), 35 parts of itaconic acid, 8 parts of imidazolidinone, 4 parts of sodium sulfite, 8.5 parts of ammonium persulfate, 0.9 parts of polycarboxylic acid water reducer, 0.9 parts of sodium gluconate, and 80 parts of water.
[0180] In 80 parts of water, add 130 parts of AMPS, 35 parts of itaconic acid, heat to 70 degrees Celsius, add 8 parts of imidazolidinone, 4 parts of sodium sulfite, 8.5 parts of ammonium persulfate, fully dissolve, heat to 75 degrees Celsius, keep warm for 2 hours, add 0.9 parts of polycarboxylate water reducer and 0.9 parts of sodium gluconate, the temperature rises to 80 degrees Celsius after adding, record the temperature and set the temperature section to keep warm for 4 hours to prepare the retarder. After the insulation is completed, cool to room temperature, and the polymer pH is measured to be 7.0, which meets environmental protection requirements.
[0181] Performance evaluation: The cement-based slurry (blank control group) was: 500g of G-grade cement + 300g of quartz sand + 336g of distilled water + 1.6g of GWX-1L.
[0182] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0183] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0184] Carry out the experiment at 240 degrees Celsius and 120mPa in accordance with Chapter 4 of SY / 5546-92, record the thickening time, and also record the 48-hour strength test value and enter it into Table 18.
[0185] Table 18
[0186] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 86 22.3 Experimental Group 1 236 16.2 Experimental Group 2 208 10.0
[0187] As shown in Table 18, the thickening time of the slurry with the prepared retarder is prolonged. When the salt concentration increases, the thickening time of the slurry is prolonged, indicating that the prepared retarder has both temperature resistance and salt resistance. The slurry has the properties of not thickening at low temperatures and not diluting at high temperatures.
[0188] Example 19: Take 140 parts of AMPS (2-acrylamide-2-methylpropanesulfonic acid), 38 parts of itaconic acid, 10 parts of imidazolidinone, 5 parts of sodium sulfite, 10 parts of ammonium persulfate, 1 part of polycarboxylic acid water reducer, 1.15 parts of sodium gluconate, and 80 parts of water.
[0189] In 80 parts of water, add 140 parts of AMPS, 38 parts of itaconic acid, heat to 70 degrees Celsius, add 10 parts of imidazole, 5 parts of sodium sulfite, 10 parts of ammonium persulfate, fully dissolve, heat to 75 degrees Celsius, keep warm for 2 hours, add 1 part of polycarboxylate water reducer and 1.15 parts of sodium gluconate, the temperature rises to 80 degrees Celsius after adding, record the temperature and set the temperature section to keep warm for 4 hours to prepare the retarder. After the insulation is completed, cool to room temperature, and the polymer pH is measured to be 7.0, which meets environmental protection requirements.
[0190] Performance evaluation: The cement-based slurry (blank control group) was: 500g of G-grade cement + 300g of quartz sand + 336g of distilled water + 1.6g of GWX-1L.
[0191] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0192] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0193] Carry out the experiment at 240 degrees Celsius and 120mPa in accordance with Chapter 4 of SY / 5546-92, record the thickening time, and also record the 48-hour strength test value and enter it into Table 19.
[0194] Table 19
[0195] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 86 22.3 Experimental Group 1 230 18.5 Experimental Group 2 216 18.1
[0196] As shown in Table 19, the thickening time of the slurry with the prepared retarder is prolonged. When the salt concentration increases, the thickening time of the slurry is prolonged, indicating that the prepared retarder has both temperature resistance and salt resistance. The slurry has the properties of not thickening at low temperatures and not diluting at high temperatures.
[0197] Example 20: Take 150 parts of AMPS (2-acrylamide-2-methylpropanesulfonic acid), 38 parts of itaconic acid, 9.5 parts of imidazolidinone, 5 parts of sodium sulfite, 9.5 parts of ammonium persulfate, 0.95 parts of polycarboxylic acid water reducer, 1.2 parts of sodium gluconate, and 80 parts of water.
[0198] In 80 parts of water, add 150 parts of AMPS, 38 parts of itaconic acid, heat to 70 degrees Celsius, add 9.5 parts of imidazolidinone, 5 parts of sodium sulfite, 9.5 parts of ammonium persulfate, fully dissolve, heat to 75 degrees Celsius, keep warm for 2 hours, add 0.95 parts of polycarboxylate water reducer and 1.2 parts of sodium gluconate, the temperature rises to 80 degrees Celsius after adding, record the temperature and set the temperature section to keep warm for 4 hours to prepare the retarder. After the insulation is completed, cool to room temperature, and the polymer pH is measured to be 7.0, which meets environmental protection requirements.
[0199] Performance evaluation: The cement-based slurry (blank control group) was: 500g of G-grade cement + 300g of quartz sand + 336g of distilled water + 1.6g of GWX-1L.
[0200] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0201] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0202] Carry out the experiment at 240 degrees Celsius and 120mPa in accordance with Chapter 4 of SY / 5546-92, record the thickening time, and also record the 48-hour strength test value and enter it into Table 20.
[0203] Table 20
[0204] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 86 22.3 Experimental Group 1 320 19.5 Experimental Group 2 222 17.9
[0205] As shown in Table 20, the thickening time of the slurry with the prepared retarder is prolonged. When the salt concentration increases, the thickening time of the slurry is prolonged, indicating that the prepared retarder has both temperature resistance and salt resistance. The slurry has the properties of not thickening at low temperatures and not diluting at high temperatures.
[0206] From the above embodiments, it can be seen that:
[0207] The viscosity of the retarder prepared in Example 1-5 is too high, and the cement slurry prepared therefrom cannot be poured into the thickening slurry cup to complete the subsequent experiments;
[0208] The retarders prepared in Examples 6-9 have temperature resistance but no salt resistance;
[0209] The retarders prepared in Examples 10-21 have both temperature resistance and salt resistance.
[0210] The retarders prepared in Examples 10-14 have both temperature resistance and salt resistance, but have a greater impact on the strength of cement paste;
[0211] The retarder prepared in Examples 15-20 has temperature and salt resistance, prolonged thickening time, has little effect on the strength of cement paste, and the pH meets environmental protection requirements;
[0212] The retarder prepared in Examples 15-20 is neutral and is an ultra-high temperature resistant and low dilution oil well cement slurry retarder. The preparation method is as follows:
[0213] (1) 120-150 parts of AMPS (2-acrylamide-2-methylpropanesulfonic acid), 28-38 parts of itaconic acid, 5-10 parts of imidazolidinone, 2-5 parts of sodium sulfite and 5-10 parts of ammonium persulfate are dissolved in 80-90 parts of water; (2) 0.5-1 parts of polycarboxylate water reducer and 0.7-1.2 parts of sodium gluconate are added. Step (2) is preferably reacted at 78-80 degrees Celsius.
[0214] As further preferred, the preparation method of Examples 17-20 is as follows:
[0215] (1) 130-150 parts of AMPS (2-acrylamide-2-methylpropanesulfonic acid), 35-38 parts of itaconic acid, 8-10 parts of imidazolidinone, 4-5 parts of sodium sulfite and 8.5-10 parts of ammonium persulfate are dissolved in 80-90 parts of water;
[0216] (2) Add 0.85-1 part of polycarboxylate water reducer and 0.85-1.2 parts of sodium gluconate.
[0217] The neutral ultra-high temperature resistant low dilution oil well cement slurry retarder prepared by the present invention can be used for oil and gas production. Specifically, the neutral ultra-high temperature resistant low dilution oil well cement slurry retarder provided by the present invention is mixed with oil well cement.
Claims
1. Neutral ultra-high temperature resistant low dilution oil well cement retarder, characterized in that: The neutral ultra-high temperature resistant and low dilution oil well cement retarder is prepared by polymerization of 2-acrylamide-2-methylpropane sulfonic acid, itaconic acid and imidazolidinone, wherein the weight parts are 120-150 parts of 2-acrylamide-2-methylpropane sulfonic acid, 28-38 parts of itaconic acid and 5-10 parts of imidazolidinone respectively.
2. A method for preparing the neutral ultra-high temperature resistant low dilution oil well cement retarder according to claim 1, characterized in that: The method comprises: (1) dissolving 120-150 parts of 2-acrylamide-2-methylpropanesulfonic acid, 28-38 parts of itaconic acid, 5-10 parts of imidazolidinone, 2-5 parts of sulfite and 5-10 parts of ammonium persulfate in 80-90 parts of water; (2) adding 0.5-1 parts of polycarboxylic acid water reducer and 0.7-1.2 parts of gluconate.
3. The method according to claim 2, characterized in that Step (1) is: (1) 130-150 parts of 2-acrylamide-2-methylpropanesulfonic acid, 35-38 parts of itaconic acid, 8-10 parts of imidazolidinone, 4-5 parts of sulfite and 8.5-10 parts of ammonium persulfate are dissolved in 80-90 parts of water.
4. The method according to claim 2, characterized in that Step (2) is: (2) Add 0.85-1 part of polycarboxylate water reducer and 0.85-1.2 parts of gluconate.
5. The method according to claim 2, characterized in that Step (2) is reacted at 78-80 degrees Celsius.
6. The method according to any one of claims 2 or 3, characterized in that: The sulfite is sodium sulfite.
7. The method according to any one of claims 2 or 4, characterized in that: The gluconate is sodium gluconate.
8. Use of the neutral ultra-high temperature resistant and low dilution oil well cement retarder according to claim 1 in oil and gas development.
9. An oil well cement, characterized in that: The oil well cement contains the neutral ultra-high temperature resistant and low dilution oil well cement retarder according to claim 1.
10. Use of the oil well cement according to claim 9 in oil and gas development.
Citation Information
Patent Citations
Method for preparing high-temperature-resistant and salt-resistant retarders for oil well cement
CN106811183A
Well cementation retarder
CN106928950A
Preparation method of retarder used for oil gas well cementing operation, retarder and application
CN107814876A